Annual rainfall trends in the Burkina Faso Sahel: a comparative analysis between Mann–Kendall and innovative trend method (ITM) - Joseph Yaméogo (Springer Nature, 2025)
The aim of this study is to analyse rainfall trends using the innovative trend method and the Mann–Kendall test. Rainfall data for the period 1981–2020 were obtained from the monthly CHIRPS (Climate Hazards Group Infrared Rainfall with Stations) database provided by the USGS (United States Geological Survey) to FEWSNET (Famine Early Warning Systems Network). The data were analysed using descriptive statistics and trend and Mann–Kendall tests. The study showed that rainfall data for the period 1981–2020 are subject to variability at all locations in the Sahel. In addition, annual rainfall is also subject to low, medium and high fluctuations depending on the location. The study shows an increasing trend in rainfall based on the Mann–Kendall test, while the innovative approach found high, medium and low trends. This means that the innovative method is more sensitive to local trends than the Mann–Kendall test, and it is therefore important for regional authorities to tailor their support to the reality of each Sahelian community in order to make rural populations more resilient.
Keywords: Innovative trend method · Mann–Kendall test · Variability · Rainfall · Burkina Faso